Teknologi Komunikasi Smartphone Pada Interaksi Sosial - Abdul Basit; Eko Purwanto; Agus Kristian; Dewi Intan Pratiwi; Krismira; Intan Mardiana; Gusri Weni Saputri (LONTAR: Jurnal Ilmu Komunikasi, 2022)
The use of smartphones causes several changes in the behavior of a person who tends to be complacent with his world without caring about society. Smartphones can have a positive or negative impact depending on their use. This study aims to determine whether there is an influence of smartphone communication technology on social interaction. The research method used quantitative methods, the population was carried out at PT Paragon Technology and Innovation with a sample of 150. The results showed that there was an influence in it, that smartphone communication technology has links with users related to the process of social interaction, this can be proven by how someone uses communication tools in everyday life. The social interaction built by employees within the company seems to be very good, this is evidenced by the hypothesis obtained from data processing that smartphone communication technology in every interaction with colleagues has no effect. The interaction process will run well if it is done with face-to-face communication, without any interference from the communication tool, namely smartphones.